PENGARUH KOMITMEN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA BADAN PUSAT STATISTIK KABUPATEN SERANG - Rozi, Achmad; Sandra, Mela; Maulana, Iqbal (DESANTA (Indonesian of Interdisciplinary Journal), 2024)
For government agencies, the availability of quality, highly skilled and professional human resources is a requirement in order to improve the quality of state administration which provides satisfaction with the quality and services produced by the government to the community. Apart from commitment, employee competency is another important factor that greatly contributes to improving employee performance in an organization. This research aims to determine the influence of commitment and competence on the performance of employees of the Serang Regency Central Statistics Agency. This research uses a quantitative research method, namely a research method that uses data in the form of numbers to analyze the facts found which aims to determine the relationship between variables in a population. This research used 37 research respondents. Based on the results of data analysis, it was found that there is an influence of commitment on employee performance, there is an influence of competence on employee performance, there is an influence of Commitment and Competence together on employee performance, with a level of influence of 76,5%. The remaining 23,5% is influenced by other factors in the scope of human resource issues, for example, discipline, organizational culture, job satisfaction and so on, which are not included in this research.